The impact of the Basel III banking regulation on Moroccan banks - Mohammed Mikou (Graduate Institute of International and Development Studies, 2023)
This paper estimates the social costs and benefits of the Basel III banking regulation application to Moroccan banks, which, inter alia, imposed higher capital requirements. The paper quantifies the impact of higher capital requirements on (i) lending rates, (ii) bank refinancing costs, and (iii) banking system resilience. Our findings indicate that the increase in capital requirements for Moroccan banks has a limited impact on lending and refinancing costs. The benefit of greater banking system resilience in terms of systemic risk appears to be more significant in expectations.
Keywords: 330; Basler Akkord; Bankenregulierung; Wirkungsanalyse; Kreditzins; Refinanzierung; Organisationelle Resilienz; Bank; Marokko